Presentase Dan Jaringan Korupsi Angelina Sondakh Pada Putusan Hakim Mahkamah Agung No 1616kPis.Sus2013 - Setiawan, Anang; Nurmandi, Achmad (UIR Law Review, 2020)
The rise of corruption cases that occur in Indonesia today, if we see corruption cases in Indonesia every year is always increasing, not decreasing, this causes people to feel angry with corruptors. The percentage and network of corruption Angelina Sondakh of the Supreme Court Judge's Decision No. 1616k / Pis.Sus / 2013 is quite interesting to examine especially if we can see who the dominant actors are in this case, both from the planning process, the bidding process, the bid evaluation process, and implementation and evaluation. This study uses a descriptive qualitative approach which illustrates the phenomenon of Angelina sondakh corruption case in the Supreme Court's Decision No. 1616 K / Pid.Sus / 2013. Descriptive analysis in this study uses the Nvivo 12 Plus software. Data from this study were sourced from the Supreme Court Decision No. 1616 K / Pid.Sus / 2013 and previous research relating to the Corruption of Angelina Sondakh. The results of this discussion The conclusions that the author can take from the presentation of the analysis above are based on the decision of the Supreme Court No. 1616 K / Pid.Sus / 2013 analyzed with Nvivo 12 Plus in general from the four processes above can be seen Corporate 9.05%, Government 7.62%, Political Parties 0.32% and Political Consultants 0%. Keyword: Corruption; Bribery; Network